Dietary Diversity, Diet Quality, and Body Weight Regulation. (25th September 2014) - Kennedy, Eileen
Abstract : Is dietary variety good or bad? The answer depends on how the variety is defined and the outcome of interest. The evidence for overall diet quality and food security still suggests that variety in consumption patterns is a net plus. However, variety in certain selected foods— energy-dense foods, for example—may contribute to overweight and obesity. The issue for overweight and obesity is clearly energy balance; results presented in this paper suggest that energy balance is harder to achieve with diets high in total fat and energy.